Effects of the Rho-Kinase Inhibitor Y-27632 on Extraocular Muscle Surgery in Rabbits - Ji‐Sun Moon; Hyun Kyung Kim; Sun Young Shin (Journal of Ophthalmology)
Purpose. To evaluate the effect of the Rho-kinase inhibitor Y-27632 on postoperative inflammation and adhesion following extraocular muscle surgery in rabbits. Methods. The superior rectus muscle reinsertion was performed on both eyes of 8 New Zealand white rabbits. After reinsertion, the rabbits received subconjunctival injections of the Rho-kinase inhibitor and saline on each eye. To assess acute and late inflammatory changes, Ki-67, CD11β+, and F4/80 were evaluated and the sites of muscle reattachment were evaluated for a postoperative adhesion score and histopathologically for collagen formation. Results. F4/80 antibody expression was significantly different in the Rho-kinase inhibitor-injected group at both postoperative day 3 and week 4 (p=0.038, 0.031). However, Ki-67 and CD11β+ were not different the between two groups. The difference in the SRM/conjunctiva adhesion score between the two groups was also significant (p=0.034). Conclusion. Intraoperative subconjunctival injection of the Rho-kinase inhibitor may be effective for adjunctive management of inflammation and fibrosis in rabbit eyes following extraocular muscle surgery.